An integrated larval development and population genetics approach for predicting the establishment and dispersal potential of a recently introduced polychaete (Annelida: Spionidae) in southern Africa - David, Andrew Anthony (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD) -- Stellenbosch University, 2015.